(untitled) (CAHIERS MAGELLANES-NS, 2024)
The right to good governance has been intrinsic in the Indian Constitution and to enforce the same the government came up with the Right to Information Act. Good governance is nothing but the procedure or the process of analyzing the situation and the needs of the society to arrive at a decision that can further help in achieving the desired developmental goals of the nation. For the longest time in history, the focus of the governance system has been to ensure that basic human and fundamental rights are protected, but there has been a shift in the approach over the past two decades where the government and the judicial organs have started focusing on the social and economic rights of the citizens along with other civil and political rights. Indian Courts always had the power to enforce the rights provided under Part III of the Constitution but could not do so for Part IV, which was solely a matter of concern for the executive wing. But the courts have successfully found a way to enforce these rights and have through recent judgments directed the government, balancing the civil and political rights with socio-economic rights. The researchers in this paper will emphasize the concept of good governance while analyzing how constitutionalizing socio-economic rights is crucial for enforcing the right to good governance. In the next section, the researcher will study the shift in the approach of the government and policy initiatives taken to enforce socio-economic rights. Then the researcher will focus on the judicial approach, trying to comprehend how the courts have harmonized fundamental rights and directive principles to give powers to themselves for the enforcement of Part IV of the Constitution. Lastly, while concluding the research paper, researchers will try to list down the possible mechanisms that can be adopted for the effective enforcement of socio-economic rights in India.